Blue rubber bleb nevus syndrome in a Malay girl: A case report and literature review - Fatimah Mat Johar; Wan Azman Wan Sulaimana; Arman Zaharil Mat Saad; Normala Basiron; Nik Amin Sahid (2020)
INTRODUCTION: Blue Rubber Bleb Nevus Syndrome (BRBNS) also known as Bean’s Syndrome is an atypical type of vascular malformation. To date, around 200 cases have been reported world-wide. In view of its low incidence rate, clinicians might misdiagnose and under treat. The key features of this syndrome are characterized by multiple cutaneous, soft tissue and gastrointestinal tract venous malformations. PRESENTATION OF CASE: We report the first case of Blue Rubber Bleb Nevus Syndrome in Malaysia, a 23 years old Malay girl who suffers from multiple cutaneous venous malformation and gastrointestinal bleeding episodes. DISCUSSION: The typical morbidity for this syndrome is symptomatic anemia due to secondary iron deficiency due to the gastrointestinal venous malformation bleeding. In managing the gastrointestinal bleeding, it mainly depends on the severity of gastrointestinal bleeding, some may resolve spontaneously, while the others may be needing blood transfusion, and some may require GIT resections. As for cutaneous lesions, normally it is innocuous depending on the region and size. Large or problematic cutaneous venous malformation might benefit from sclerotherapy or excision. CONCLUSION: Multidisciplinary approach is crucial in managing BRBNS case due to its complexity and the spectrum of multiple organ involvement to ensure the best outcome to the patient